Perception and awareness of patients regarding ovarian cysts in Peshawar, Pakistan: A qualitative approach - Almas, Iffat; Rehman, Nisar-ur-; Azhar, Saira; Ismail, Mohammad; Murtaza, Ghulam; Hussain, Izhar (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study: Women health is one of the key issues in developing countries including Pakistan. To improve the women’s quality of life, awareness about health is necessary.The objective of this study is to evaluate the patient’s perception regarding ovarian cyst and the awareness of the patients about the symptoms and health management in ovarian cyst. Material and methods: A qualitative approach was used to conduct this study. An interview guide was prepared for the data collection. The interview guide had 29 questions which were asked from the patients. The duration of each interview was about 15–20 minutes and conducted in native language (Urdu) which was then translated to English language for the purpose of documentation. Snowball technique was adopted and the sample size was estimated from the point of saturation. Results: All the interviews were conducted in the Gynecology ward of Hayatabad Medical Complex (HMC), Peshawar, Pakistan. Results were thematically analyzed. Thematic content analysis yielded 5 major themes: 1) Ir-regular menstrual cycle, 2) nausea and vomiting, 3) difficulty in emptying urinary bladder completely, 4) emergency due to severe pain, and 5) Physical works. Conclusions : There is a need of time that patients should be counseled at the time of discharge of the patient from the hospital. This is the right of the patient that they know about their disease and benefits of the successful treatment outcomes. Compliance can only be achieved through the counseling of the patients, resulting good quality of life and less economic burden over the patients.